Pancasila dan pendidikan anti korupsi: Peran pendidikan pancasila terhadap pembentukan sikap anti korupsi mahasiswa generasi z - dewi, ayu fitri (Maliki Interdisciplinary Journal, 2025)
Corruption is an extraordinary crime that not only harms the country economically, but also damages the moral, social, and spiritual values of the nation. This act stems from low integrity and weak moral awareness of individuals regarding the values of honesty and responsibility. In the context of education, the role of Pancasila Education is very important as a means of shaping anti-corruption character from an early age. Through learning that emphasizes Pancasila values such as justice, honesty, and social responsibility, students are guided to internalize integrity and avoid corrupt behavior. Generation Z, as future leaders, needs to be equipped with strong critical and moral awareness amid rapid technological developments and information flows. Educators play an important role in instilling values of integrity through contextual, creative, and project-based learning methods. Thus, eradicating corruption does not only depend on law enforcement, but must begin in the world of education through continuous character building in order to realize a clean, just, and civilized nation.